2015
DOI: 10.1007/s00405-015-3721-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of endoscopic shortening and stiffening of the vocal folds to raise the pitch

Abstract: In this study, we aimed to assess the long-term effects of the mucosal layer plastic surgery of the vocal folds performed on the voices of male-to-female transgenders. This retrospective cohort study enrolled 22 patients who were operated during 2004-2010 by a combined technique of transmucosal anterior suturing and stiffening of the vocal folds through a longitudinal cordotomy incision using CO2 laser. Long-term effects were assessed based on completed questionnaires on four different categories including sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
0
27
0
8
Order By: Relevance
“…Geneid et al . () reported no correlation between mean F0 and VHI score. The findings of Remacle et al .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Geneid et al . () reported no correlation between mean F0 and VHI score. The findings of Remacle et al .…”
Section: Introductionmentioning
confidence: 91%
“…Self‐report tools are particularly important when assessing the vocal needs of the MtF woman as clinician evaluations of her voice do not necessarily reflect how her voice impacts on her everyday life (Geneid et al . , Remacle et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these procedures, the systematic review showed that other studies using surgical intervention performed over the past 10 years to increase the f0 in transsexual women were not included in the metaanalysis because they did not have a control group. The surgical procedures included cricothyroid approximation and subluxation, 4 laser-assisted voice adjustment, 7 Wendler glottoplasty, 25 anterior glottic web formation assisted by temporary injection augmentation, 26 a combined technique of transmucosal anterior suturing and stiffening of the vocal folds through a longitudinal cordotomy incision using a CO2 laser, 15 Wendler glottoplasty and voice therapy, 27 and cricoid-thyroid approximation. 28 This study also highlighted that at the presurgical time (Table IV), none of the studies had an EG (experimental group) with f0 within the range considered female (150-250 Hz), except the CG (control group) of one study that was composed of cis-sexual women.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures often are implemented when the speech therapy was not satisfactory and the individual is constrained by not being able to sustain an f0 without fatigue—or by having a deep pitch during laughter, coughing, yawning, screaming, or throat‐clearing. Moreover, after surgical elevation of f0, the individual does not need to think about the voice frequency or imitate female voices …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation